Cervical spondylotic internal jugular venous compression syndrome. (22nd May 2019) - Ding, Jia‐Yue; Zhou, Da; Pan, Li‐Qun; Ya, Jing‐Yuan; Liu, Cheng; Yan, Feng; Fan, Chun‐Qiu; Ding, Yu‐Chuan; Ji, Xun‐Ming; Meng, Ran
Abstract: Aims: This study aimed to identify the clinical profiles of cervical spondylosis‐related internal jugular vein stenosis (IJVS) comprehensively. Methods: A total of 46 patients, who were diagnosed as IJVS induced by cervical spondylotic compression were recruited. The clinical manifestations and imaging features of IJVS were presented particularly in this study. Results: Vascular stenosis was present in 69 out of the 92 internal jugular veins, in which, 50.7% (35/69) of the stenotic vessels were compressed by the transverse process of C1, and 44.9% (31/69) by the transverse process of C1 combined with the styloid process. The transverse process of C1 compression was more common in unilateral IJVS (69.6% vs 41.3%, P = 0.027) while the transverse process of C1 combined with the styloid process compression had a higher propensity to occur in bilateral IJVS (52.2% vs 30.4%, P = 0.087). A representative case underwent the resection of the elongated left lateral mass of C1 and styloid process. His symptoms were ameliorated obviously at 6‐month follow‐up. Conclusions: This study proposes cervical spondylotic internal jugular venous compression syndrome as a brand‐new cervical spondylotic subtype. A better understanding of this disease entity can be of great relevance to clinicians in making a proper diagnosis.